2016
DOI: 10.1016/j.applthermaleng.2016.04.130
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and mixing enhancement by using multiple freely oscillating flexible vortex generators

Abstract: h i g h l i g h t s Self-sustained oscillations of flexible vortex generators without any external force except that of the fluid flow. Increase in the oscillations amplitude is obtained by increasing the system degree of freedom. The effect of flaps number and arrangement on heat and mass transfer enhancement applications in static mixers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…After a transient period, the FVG undergo self sustained large displacement oscillation with a frequency approximately equal to their natural frequency. Meanwhile FVG located in rows B and D show small oscillation amplitudes, much more FVG interaction is obtained in rows A, C and E. This observation is particularly relevant with previous results obtained in two-dimensional FVG configurations (Ali et al, 2016) where three successive flaps were needed to reach a self-sustained oscillating system. For future full three-dimensional simulations, it is thus to be expected that adding a sixth tangentially rotated row F may have drastic effect on the oscillation of FVG located in rows B and D. Moreover, it is observed that for a given row, tabs located at the north and south positions always oscillate out of phase with tabs located at the east and west positions.…”
Section: Resultssupporting
confidence: 83%
“…After a transient period, the FVG undergo self sustained large displacement oscillation with a frequency approximately equal to their natural frequency. Meanwhile FVG located in rows B and D show small oscillation amplitudes, much more FVG interaction is obtained in rows A, C and E. This observation is particularly relevant with previous results obtained in two-dimensional FVG configurations (Ali et al, 2016) where three successive flaps were needed to reach a self-sustained oscillating system. For future full three-dimensional simulations, it is thus to be expected that adding a sixth tangentially rotated row F may have drastic effect on the oscillation of FVG located in rows B and D. Moreover, it is observed that for a given row, tabs located at the north and south positions always oscillate out of phase with tabs located at the east and west positions.…”
Section: Resultssupporting
confidence: 83%
“…There are several published papers about using VGs in forced convective flows. It was concluded that the vibration of elastic VG enhances the convection heat transfer by flo w mixing and breaking the thermal boundary layer adjacent to the heated surfaces [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also suggest novel non-traditional applications of passive flag flapping to reduce turbulent effects (Shen et al 2003), to increase propulsion efficiency (Shoele & Zhu 2013), and to enhance heat transfer in packaged electronics (e.g. Shoele & Mittal 2014;Ali et al 2016). The large amplitude flow-induced oscillations are the basis of some energy harvesting concepts (e.g.…”
Section: Introductionmentioning
confidence: 99%